Assessment of the Biochemical Status of Women in Labor with Preeclampsia - Giozovna, Yuldasheva Gulnoz; Bobokulovich, Rustamov Bakhtiyor (Journal of Medical Genetics and Clinical Biology, 2024)
This review presents the results of scientific work on the study of the immuno-biochemical status of women in labor with preeclampsia. Indicators of developing problems in the body of a pregnant woman are changes in the biochemical composition of the blood, which make it possible to predict maladaptation syndrome in newborns.